Socioeconomic Disparities in Iranians' Preferences toward Dental Care Services: A Population-Based Survey - Mohammad Khajedaluee; Zahra Yaghoubi; Tayebeh Malek Mohammadi; Kosar Sadat Hosseini (Hindawi Limited, 2022)
Background and Aims. Patients' perspectives and preferences are considered an essential influencing factor for healthcare utilization. This study is one of the first to investigate patient preference for dental services across socioeconomic and demographic indicators in Iran. Materials and Methods. This cross-sectional study was conducted through telephone interviews with adult residents in Mashhad and Kerman cities. A representative sample was selected by stratified random sampling. A valid structured questionnaire was used for data collection, including people's preference toward dental care services in terms of dental settings, choosing a general or specialist dentist, prevention or treatment, and the preferable gender of the dentist. Factors potentially associated with preferences included gender, age, educational level, job, monthly income, house size, family number, insurance coverage, dental insurance, type of insurance, and social class in the city were investigated. Results. 1475 individuals participated in the study [response rate 63%]. Our findings showed higher preferences for private offices (50.6%), specialist dentists (76.2%), treatment services (40.8%), and no specific gender preference for the dentist (60.6%). Their preferences were significantly influenced by age range, social class, insurance status, dental insurance, and type of insurance. Income, household size, level of education, and job were not statistically significant with none of the preferences. Conclusions. Socioeconomic and demographic factors' correlation with people's preferences was observed. Efforts are needed to promote preventive care demand in deprived regions. Moreover, increasing financial resources allocated to preventive care and covering preventive dental services in insurance plans are recommended.